Effication of Convalence Plasma Therapy in Covid-19 Patients: Systemic Review and Meta – Analysis - Diyono, Diyono; Sriwiyati, Lilik (Jurnal Kesehatan Holistic, 2022)
Introduction: COVID-19 has developed into a global pandemic and until now no definitive therapy has been found. COVID-19 mortality is relatively high, especially in patients who have comorbidities. Convalescent plasma therapy, which has been widely used, has not been universally recognized as being able to improve the recovery of COVID-19 patients. Objective: This study aims to determine the efficacy of convalescent plasma therapy in COVID-19 patients. Methods: The research design is a systematic review and meta analysis. Data were obtained from the electronic journal database PubMed, Cochrane Library, ProQuest, SpringerLink, ScienceDirect, Scopus, and Google Scholar with Medical Subject Heading (Mesh) "Effication Plasma Convalescent Therapy, SARS CoV-2". Data were analyzed using PRISMA guidelines. Result: The results of the study: 1) There was no difference in the risk or mortality rate of Covid-19 patients given convalescent plasma therapy with those given standard therapy (OR: 1.004; CI; 0.817 - 1.234; p = 0.970), 2) The recovery rate of COVID-19 patients given convalescent plasma therapy did not differ from those given standard therapy (OR: 0.996; CI: 0.810 – 1.224; p = 0.970). Conclusion: convalescent plasma therapy did not provide sufficient efficacy in the healing process of COVID-19 patients with moderate to severe symptoms.